The Importance of Peer Quality for Completion of Higher Education - Maria Knoth Humlum; Mette Thorsager (Institute of Labor Economics (IZA), 2021)
Using detailed Danish administrative data covering the entire population of students entering higher education in the period 1985 to 2010, we investigate the importance of a student's peers in higher education for the decision to drop out. We use high school GPA as a predetermined measure of student ability and idiosyncratic variation in peer composition across cohorts within the same education and institution. Our findings suggest that peer ability is an important determinant of students' drop out decisions as well as later labor market outcomes. Overall, we find that a one standard deviation increase in peers' high school GPA reduces the probability of dropping out by 4.6 percentage points. This number masks considerable heterogeneity by level and field of study. Allowing for a more flexible specification, we find that low quality peers have adverse effects on the probability of dropping out while high quality peers have beneficial effects. These effects are more pronounced for lower ability students.
Keywords: I21; I24; 330; dropout; peer effects; peer quality; higher education